Geometric Study of Polymer Embedded Micro Thermoelectric Cooler with Optimized Contact Resistance - Dutt, Aditya S.; Deng, Kangfa; Li, Guodong; Pulumati, Nithin B.; Ramos, David Alberto Lara; Barati, Vida; Garcia, Javier; Perez, Nicolas; Nielsch, Kornelius; Schierning, Gabi; Reith, Heiko (Advanced Electronic Materials, 2022)
Micro-thermoelectric devices (μTEDs) are used for bio-medical applications, powering internet-of-things devices, and thermal management. For such applications, μTEDs need to have a robust packaging so that the devices can be brought in direct thermal contact with the target heat sink and source. The packaging technology developed for macroscopic modules needs improvement as it cannot be applied to μTEDs due to a large thermal resistance between the capping material and the device which deteriorates its performance. In this work, μTEDs with high net cooling temperature are fabricated by optimizing the contact resistance and device design combined with a novel packaging technique that is fully compatible with on-chip integration. The simulations and experiments demonstrate that the additional thermal loss caused by the packaging leads to an only marginal decrease in the net cooling temperature. The devices achieve a high net cooling temperature of 10.8 K without packaging and 9.6 K with packaging at room temperature. The packaging only slightly increases the thermal response time of the devices, which also shows an extremely high reliability of over 85 million cooling cycles. This simple packaging technique together with robust device performance is a step toward wide-spread application of μTEDs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: contact resistance; electrochemical deposition; micro-thermoelectric devices; packaging; TEC design; TEC reliability; thermoelectrics